Study on shear mechanisms of UHPC-NC reinforced interfaces and grooved & reinforced interfaces - Tian, Jing; Jiang, Xinghong; Yang, Xinan; Li, Luheng; Li, Jingtao (Case Studies in Construction Materials, 2025)
Understanding the shear mechanisms of both reinforced and grooved & reinforced UHPC-NC interfaces is crucial for designing and applying UHPC-NC composite arch structures. In this study, double-shear tests were conducted on these two interface types, with systematic variations in reinforcement spacing and diameter. Based on the analysis of the failure mechanisms, calculation methods for the shear capacity of both interface types were developed. The results revealed two distinct failure modes in the reinforced interface: steel-shear failure and NC-splitting failure. Conversely, the grooved & reinforced interface exclusively exhibited NC-splitting failure. The shear strength of reinforced interfaces shows a proportional increase with reduced rebar spacing, while interfacial slip demonstrates an inverse correlation. Similarly, both interfaces exhibit enhanced shear strength and reduced slip with larger rebar diameters. Analysis of load-slip curves reveals four distinct stages, demarcated by critical transitions in reinforcement stress states. Furthermore, interfacial slip serves as a reliable indicator for deciphering shear-resistance mechanisms in both interfaces. The reinforced interface failed when the rebar dowel force reached either the rebar's ultimate tensile capacity or the NC splitting force. Failure of the grooved & reinforced interface occurred when rebar dowel force increases to the NC splitting force after the groove-induced shear remains at post-transition groove-induced shear resistance. The NC splitting force is proportional to both the spacing and diameter of the reinforcement. The proposed formula can accurately predict the shear capacity of both interface types. The result is a clear guidance for the calculation of the shear strength of UHPC-NC grooved & reinforced interface. •The shear bond properties of reinforced and grooved & reinforced interfaces were experimentally tested.•Interfacial slip reliably indicates shear resistance mechanisms in both interfaces.•The reinforced interface's two failure modes depend on NC splitting force versus single rebar ultimate bearing capacity.•Grooved & reinforced interface fails when rebar force reaches NC splitting force after groove shear settles to its capacity.•The diameter and spacing of interface rebar are key factors influencing the NC splitting force.